High performance of a flexible graphene nanoplatelets supercapacitor in a stacked configuration - Chiam, Sin Ling (2018)
The energy density and working potential of conventional supercapacitor devices are in the range of 6–10 Wh/kg, which has hindered it to be implemented in electronic applications that required devices to run in a long durations at a higher voltage. Herein, we report a method for enhancing the energy density of a device through the parallel stacking of five copper foils electrodes coated with graphene nanoplatelets as electroactive material. Microporous papers immersed in 2 M of aqueous sodium sulphate electrolyte were then used as separators in between stacked copper foils to complete the supercapacitor device. The as-assembled supercapacitor had achieved a specific capacitance value of 142 F/g with low contact resistance of 0.05 Ω at 1 A/g. The supercapacitor yielded optimum specific energy and specific power density of 24.64 Wh/kg and 402 W/kg at 0.8 V, respectively. Furthermore, the utilization of copper foil current collector and microporous paper type separator give additional merit of flexibility to the supercapacitor when an unnoticeable difference in cyclic voltammetry curves was observed even at 45°, 90° and 180° bending angles. The supercapacitor bent up to 180° was able to maintain high capacitance retention up to 83% after 800 cycles of continuous charge discharge cycles. Interestingly, the working potential has been successfully increased up to 2.4 V when three of the stacked supercapacitors were connected in series by forming a tandem device while bended at 180 °C. Its potential for real application was manifested by the ability to light up a light-emitting diode for 40 s when charged for 60 s. Besides that, when comparing it with the commercial available supercapacitors (KEMET, ILLINOIS), the as-assembled supercapacitor was found to outperform it in terms of energy density. Overall, the electrochemical performance tests have demonstrated the high performance of aqueous-based flexible graphene nanoplatelets supercapacitor from stacked copper foils configuration. This was found to be mainly contributed to the proper selection of each supercapacitor components from the electrode active material, current collector, electrolyte and separator through systematic analysis of spectroscopy, microscopy and electrochemical characterizations. The study that has been discussed in this thesis could pave a way to be applicable in wearable electronic devices that required high energy density and working potential before it can be implemented.